HEDONIC TESTING OF MILKFISH COOKIES WITH ADDED MORINGA LEAVES AS COMPLEMENTARY FOOD FOR PREGNANT WOMEN TO PREVENT STUNTING IN NUNUKAN - Siti Hajar; Jemri Jemri; Sri Astika; Jifa Jifa; Alifah Alifah (Asian Journal of Aquatic Sciences, 2026)
Chronic Energy Deficiency (CED) in pregnant women occurs due to nutritional deficiencies due to insufficient energy and nutrient intake, which can endanger the mother's health and cause fetal growth retardation. This condition can be prevented by providing supplementary feeding (PMT) to balance nutritional intake and to avoid stunting from in utero (1). Stunting can occur in utero and is only visible when the child is two years old. Based on data from the Central Statistics Agency (BPS) of Nunukan Regency, the number of babies born with low birth weight (LBW) increased from 225 babies (2022) to 353 babies (2023), while the number of babies with malnutrition increased from 192 babies to 391 babies in 2023 (2). The urgency of this study is the provision of complementary foods in the form of cookies for pregnant women from processed milkfish with additional nutritional value from moringa leaves for early stunting prevention in Nunukan Regency, North Kalimantan Province. Processed cookies are very important for pregnant women to achieve optimal nutritional adequacy. The purpose of this study is to test the hedonic (level of preference) and proximate testing on cookies made from milkfish (Chanos chanos) with the addition of moringa leaves (Moringa oleifera) as an effort to overcome the problem of malnutrition cases, especially about stunting that starts from mothers during pregnancy or pregnancy as an early prevention so that children are not born with a large birth weight (LBW), especially in Nunukan Regency, North Kalimantan. The research method was a survey to measure the level of preference or acceptance of milkfish cookies containing nutrients from moringa leaves among pregnant women, with 30 panelists. Complementary foods were analyzed for preference levels to assess the innovation's acceptance in the processing of these cookies. The results of the proximate analysis of this cookie product that still do not meet the requirements are the water and ash content. Meanwhile, the nutritional content of cookies according to SNI 01-7148-2005 (special drinks for pregnant and/or breastfeeding mothers) and SNI 2973.2022 (biscuits) has met the quality requirements for protein, fat, and carbohydrate levels. Meanwhile, hedonic testing using SPSS version 27 with Duncan analysis for color parameters yielded 4.40; aroma, 4.07; texture, 4.33; taste, 4.10; aftertaste, 4.13; and overall, 4.13. These results indicate that all sensory attributes, aroma, texture, taste, aftertaste, and overall acceptance, were categorized as "liked," suggesting that the product has a good level of acceptance among the panelists